Rancang Bangun Sistem Kendali Presisi Suhu dan Kelembapan pada Mesin Penyangrai Kopi Menggunakan Sensor SHT-31 - Alex Surapati; Muhammad Arfan; Warnisa Gulo; Muhammad Khairul Amri Rosa; Natsir Habibullah (Department of Electrical Engineering, UNJANI, 2025)
Conventional coffee roasting methods often face challenges regarding quality inconsistency due to a high reliance on operator proficiency and the absence of precise thermal regulation. This study aims to design and build an automatic coffee roasting system based on the Arduino Uno microcontroller integrated with an SHT-31 sensor for real-time monitoring of steam temperature and humidity. The system applies threshold control logic with a setpoint of 90°C temperature and 12% humidity to automate the servo motor actuator on the gas valve. Operational testing was conducted using coffee bean load variations of 50, 100, 150, and 200 grams. The results showed that increasing bean mass was directly proportional to roasting duration, ranging from 12.46 minutes for a 50-gram load (dark roast) to 21.16 minutes for 200 grams (light roast). Sensor reading accuracy was validated with an error value of 2.62% compared to a standard thermometer. The control system proved effective in stabilizing microclimate parameters and terminating the process automatically upon reaching targets, thereby ensuring final product consistency.